CONCEPT MAPPING AND THEORETICAL LEARNING OF NURSING STUDENTS - A. Rahmani; A. Fathi Azar; A. Mohajel Aghdam (Iran University of Medical Sciences, 2005)
Critical thinking and problem solving abilities are vital skills in nursing, enhancing these skills, nursing educators should use different educational strategies.   Therefore, to determine the effect of concept mapping on the students' meaningful learning, which is one of the ways to critical thinking, we conducted an experimental study designed with two groups. 45 second semester nursing students were selected and randomly assigned in two groups (the experimental N=24, the control N=21). The experimental group received the concept mapping treatment while, the control one treated just with traditional teaching method. For gathering data, we used an achievement test that consist of two parts (knowledge and meaningful learning).   Results showed that these two educational strategies were useful in enhancing knowledge and meaningful learning about nursing process (P=0.001). In comparison, the average score of experimental group, in knowledge test, was higher than the control one, but this didn't showed a statistically significant difference (P= 0.21). In meaningful test, also, the average score of experimental group was more than control group and this difference was statistically meaningful (P= 0.03).   Considering that the positive effect of concept mapping was revealed in this study, we suggest nursing educators to use it, especially in courses in which deep understanding is critical.